Designing perennial crop-based agroforestry systems: specificities, challenges, and opportunities - Anne Merot; Alexis Thoumazeau; Aude Alaphilippe; Margot Challand; Timothée Cheriere; Stéphane de Tourdonnet; Frédéric Gay; Marie Gosme; Marie-Hélène Jeuffroy; Pierre-Éric Lauri; Aurélie Metay; Martin Notaro; et al. (Agroforestry Systems, 2026)
Diversification of farming systems at plot scale is increasingly seen as an essential option to meet agriculture sustainability challenges and support agroecological transition. Significant progress has been made in recent years on methods for designing diversified cropping systems based on annual crops. However, few methods have been tested for designing diversified cropping systems based on perennial crops, and in particular perennial crop-based agroforestry systems, despite their important dietary and economic roles in the world. In this study, we argue that the characteristics of perennial crops induce specific structural and functional changes that impact the design process. We identified four key concepts for the design of diversified perennial crop-based agroforestry systems: (i) the targeted productivity must be considered over the long term and at the plot level, and encompass not only the productive and non-productive stages of perennial crops but also of associated plants; (ii) these systems will eventually face shocks and crisis in their lifetime, so they should be designed with resilience and adaptability in mind; (iii) initial designs will necessarily evolve throughout the long lifespan of perennial crops, and so a combination of de novo design from scratch and step-by-step design approaches for regeneration or transformation will be required; and (iv) due to the high complexity of these systems and the difficulty of setting up trials, the design process should draw from a range of knowledges from academics and practitioners and hybrid them. These four key features show that perennial crops offer distinct opportunities for the design of sustainable diversified cropping systems, but also face specific challenges that require more transdisciplinary research.

Structure and management of traditional agroforestry vineyards in the high valleys of southern Bolivia - Pablo Oliva Oller; Martin Notaro; Erick Langer; Christian Gary (Agroforestry Systems, 2022)
In the south of Bolivia, a group of traditional wine growers are distinguished by the cultivation of grapevines on native trees that serve as tutors. These growers currently represent one of the few examples of agroforestry vineyards in the world. They offer an opportunity to analyze the structure and management of these cropping systems, and to identify the ecosystem services provided by the combination of grapevines that are trained on trees. We characterize 29 agroforestry vineyards located in three high valleys in southern Bolivia, describing the main farm features, the structure and management of the vineyards, and the advantages of on-tree vine staking as recorded by the farmers. Farms were small (2.2 ha on average), with about half viticulture and half other crops and forage. The workforce was about half family and half employees. The most commonly used tree species were the molle tree ( Schinus molle ) and chañar tree ( Geoffroea decorticans ), and the majority of grape varieties grown were landraces such as “Negra criolla” and “Vicchoqueña.” The main cultivation techniques were pruning of the trees and vines, application of manure more than mineral fertilizers, gravity irrigation, and application of few pesticides. The main services farmers expected from trees were protection against climate hazards and flooding, disease control, maintenance of soil fertility, and higher yields. Agroforestry is a promising option for the agroecological transition of viticulture, which deserves further studies at both plot and farm scales.